2007
DOI: 10.1200/jco.2006.10.1535
|View full text |Cite
|
Sign up to set email alerts
|

Chromogranin A: Is It a Useful Marker of Neuroendocrine Tumors?

Abstract: Our study confirms the high specificity and sensitivity of CgA in diagnosing an endocrine tumor. It is necessary to use a cutoff range of 84 to 87 U/L to obtain a high specificity in diagnosing NETs, with the aim of excluding patients in whom the CgA was elevated as a result of other non-neoplastic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
137
1
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(155 citation statements)
references
References 26 publications
(31 reference statements)
8
137
1
6
Order By: Relevance
“…A number of putative tumour markers are measured in NET patients, with CgA having the highest expression in NETs and being considered the most useful diagnostic and prognostic marker (Janson et al, 1997;Turner et al, 2006;Campana et al, 2007). Tumour markers are measured at regular intervals and may be useful for monitoring disease progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of putative tumour markers are measured in NET patients, with CgA having the highest expression in NETs and being considered the most useful diagnostic and prognostic marker (Janson et al, 1997;Turner et al, 2006;Campana et al, 2007). Tumour markers are measured at regular intervals and may be useful for monitoring disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, tumour markers can have prognostic value: plasma neurokinin-A has been shown to be an accurate marker of prognosis in midgut NETs, with rising neurokinin-A levels despite somatostatin analogue therapy shown to be associated with poorer prognosis (Turner et al, 2006); patients with CgA greater than 5000 mg l À1 have a 5-year survival of only 22% as opposed to 63% for patients with serum chromogranin-A levels of less than 5000 mg l À1 (Janson et al, 1997). Absolute plasma CgA levels may also help to differentiate between localised and diffuse NET spread, as well as between chronic active gastritis and NETs (Campana et al, 2007).…”
mentioning
confidence: 99%
“…A különböző endokrin szö-vetekben proteolitikus módosításokat követően alakul át extracellulárisan működő biológiailag aktív peptidformákká. A CgA-ból kialakuló fehérjék, mint a pancreastatin, a vasostatin, a WE-14 és további formák jelentős és specifi kus biológiai hatással rendelkeznek (1. táblázat) [26,27,28,29,30,34,35,45,47,48,49,50,51,52].…”
Section: Következtetésekunclassified
“…Concentrations may be dependent on tumor features, such as: type, secretory activity, neuroendocrine differentiation degree and total burden (1,2). However, several lines of evidence show that the diagnostic accuracy is affected primarily by the type of assay used to measure CgA (1,(3)(4)(5). As a matter of fact, it has been reported that in healthy subjects, there is a discordance rate of ;20% between CgA concentrations measured using the two commercially available methods: immunoradiometric assay (IRMA) and enzyme-linked immunosorbent assay (ELISA) (1).…”
Section: Introductionmentioning
confidence: 99%